The Role of Community Policing for Law Enforcement in Resolving Issues Outside of Court - Saharuddin Saharuddin; Albert Pede; Yudin Yunus; Siti Alfisyahrin Lasori; Safrin Salam (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2022)
The role of the Community Development Unit (Binmas) of the Bone Bolango Police is very important. Its existence can be one of the efforts to prevent crime through community-based prevention efforts. The type of research used is empirical legal research. The results show that the role of the Community Development Unit (Binmas) of the Bone Bolango Police is being played with an emphasis on improving the efficiency and technical capabilities of the police, but it still has shortcomings because even though the handling or resolution of problems that occur in the community is only a matter of violations, minor crimes need to be improved. The inhibiting factors are first in terms of the quantity of the number of personnel; second, the supporting facilities or facilities are still minimal; and thirdly, the lack of legal awareness of the community participating in counseling or socialization activities.